Estudo de alternativas para seleção de variedades de soja (Glycine max (L.) Merril) em Uberaba, Minas Gerais - Eustáquio Arantes, Neylson; Sediyama, Tuneo; Silva, José Carlos; Lima Thiébaut, José Tarcísio; Silva Reis, Múcio (Revista Ceres, 2025)
Fourteen soybean cultivars of the maturity groups V to IX were evaluated in five planting dates from October to December, during three years (1976, 1977 and 1978), in Uberaba, Minas Gerais. The purpose was to investigate the possibility of reducing the number of years now utilized in the selection of superior varieties as based on regional tests.